PARTISIPASI MASYARAKAT SEBUAH INVESTASI UNTUK MENJAGA HRQOL PADA PEREMPUAN - Edy Purwanto; Fajar Suminto (Research Centre for Population, Indonesian Institute of Sciences, 2012)
Health Related Quality of Life focuses on health research or health related quality of life. This study l identifies the effect of community participation in HRQOL. Community participation is measured through individual participation in community activities, such as community meetings, voluntary work, PKK, Posyandu, etc. This study uses data from the Indonesian Family Life Survey 2000 and 2007. The method of analysis being used is the Two Stage Least Square (2SLS). The results of the analysis show that participation in community activity can improve HRQOL or slow down HRQOL decrease due to the age factor. This effect greater for males than for females. Using this evidence, a policy which preserves and improvesthe health status of females and health-related quality of life can be advocated by promoting more community participatory programs. Females who are active in community activities are expected to be able to preserve their health, which can reduce the effects of aging ontheir health status.Key Words: HRQOL, IFLS, Instrumental Variable, Participation.